1995
DOI: 10.1002/jemt.1070310204
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical investigation of the in vivo endocytosis by renal tubular epithelial cells

Abstract: The internalization and degradation of glomerular filtered serum proteins by the proximal tubular epithelium has been extensively studied by microperfusion methods. By using a cationic probe that easily traverses the glomerular wall into the urinary space, we have performed a morpho-cytochemical and quantitative study of the in vivo endocytotic activity of the proximal tubular epithelial cell. Bovine serum albumin (BSA) was tagged with dinitrophenol (DNP) and cationized to pI over 8. It was introduced into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…From the present TEM and AcPase investigation, it is likely that PAS-positive granules and PAS-positive giant bodies of renal S3 segment cells observed under LM are multilamellar lysosomes, probably secondary lysosomes. The lysosomes present in the proximal tubular epithelium are active endocytic organelles containing numerous hydrolases [1,3,5,[14][15][16], and the changes in size and number of the lysosomes are closely related to the stimulation of androgen and the growth and development of the animal [6,8,11]. The present study revealed sex and strain differences in lysosomal size.…”
Section: Discussionsupporting
confidence: 55%
“…From the present TEM and AcPase investigation, it is likely that PAS-positive granules and PAS-positive giant bodies of renal S3 segment cells observed under LM are multilamellar lysosomes, probably secondary lysosomes. The lysosomes present in the proximal tubular epithelium are active endocytic organelles containing numerous hydrolases [1,3,5,[14][15][16], and the changes in size and number of the lysosomes are closely related to the stimulation of androgen and the growth and development of the animal [6,8,11]. The present study revealed sex and strain differences in lysosomal size.…”
Section: Discussionsupporting
confidence: 55%
“…The brush border is an important structure for the reabsorption of macromolecules (Sumpio and Maack, 1982;Wall and Maack, 1985;Gómez-Pascual et al, 1995;Bendayan and Londoñ o, 1996). Therefore, sexual dimorphism of the PAS staining of the brush border suggests that there are differences in reabsorptive function in PST between males and females.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of acid phosphatase reaction demonstrated that these electron-dense myelinoid bodies were lysosomes, probably secondary lysosomes. The lysosomes present in the proximal tubular epithelium are endocytic organelles (Wall and Maack, 1985;Gómez-Pascual et al, 1995;Bendayan and Londoñ o, 1996) containing numerous hydrolase enzymes (Johnson et al, 1986). Moreover, lysosomal enzyme activity levels were reported to be higher in male than in female mouse kidney (Johnson et al, 1986;Koenig et al, 1980), and testosterone increases their activities (Koenig et al, 1980).…”
Section: Discussionmentioning
confidence: 99%
“…The existence of anionic sites in different cell membranes, including the apical membrane of mammalian enterocytes, has been demonstrated using cationized ferritin and other chemically modified proteins as ligand [Danon et al, 1972;Triguereo et al, 1989;Sanderson and Walker, 1993;Lehr, 1994]. The ionic interaction of a ligand with these anionic sites is usually associated with a nonreceptor mediated endocytosis that segregates the ligand to a degradative pathway within the cell [Gómez-Pascual et al, 1995]. Our results show that increasing NaCl concentrations in the binding assay only affected the specific binding, suggesting that HRP is not interacting with the broad family of anionic sites.…”
Section: Discussionmentioning
confidence: 99%